(untitled) (Revista Argentina de Musicología, 2019)
Music theory has always been fundamentally pluralistic, interdisciplinary and adaptive. However, our theoretical tradition has not left us models originating from musical practice. Throughout Modernity, musicians and music theorists have sought to explain the processes of production and musical reception based on studies of mathematics, acoustics, rhetoric, and physiology, always anchored in some philosophical strand. It is the turn of the 1980s to the 1990s that musicology has systematically faced the challenge of developing “resident” theoretical models, original in the sense of revealing and relying on specific and even exclusive experiences of our interaction with music. As a consequence of the overcoming of the otherness of the perceiver and object of musical listening (the traditional condition of objectification of musical expression), the new condition of music science has imposed the incorporation of new theoretical-methodological contributions to the production of knowledge in creative musical processes. I think the crucial problem of the discussion, at this moment, is the overcoming of the incommunicability between the “epistemic dialects” of the structuralist tradition and the embodied semantics of music, in order to reopen this field of investigation.